ISOLATION AND IDENTIFICATION OF BACTERIAL CELLULOSE PRODUCERS WITH POTENTIAL FOR MEDICINE AND BIOTECHNOLOGY - Nagmetova, G.Zh.; Kurmanbayev , A.A. (Eurasian Journal of Applied Biotechnology, 2019)
Recent achievements in investigations of microbial polysaccharides have highlighted their importance in the development of new classes of biomaterials. Some polysaccharides of microbial origin are already widely used in various medical applications, including hyaluronic acid, dextran, alginate, and scleroglucan. Substantial attention has more recently focused on bacterial cellulose as a promising and effective biopolymer. In this study, based on knowledge of the ecological niches of acetic acid bacteria, we isolated cellulose-producing bacteria using the fruits of grapes of different varieties and Kombucha. The most effective biocellulose producers were screened, and their biochemical properties were determined. A total of 17 acetic acid bacteria isolates were obtained, and three strains capable of producing a cellulose biofilm were selected, which were identified according to the direct nucleotide sequence of the 16S rRNA gene fragment and biochemical properties.